THE EFFECTIVENESS OF LEARNING PROGRAMS THROUGH BOY-BOYAN GAME TO DEPELOVE INTERPERSONAL AND INTRAPERSONAL INTELLIGENCE OF KINDERGARTEN STUDENTS KINDERGARTEN - Komala Komala (Kopertis Region IV Jabar and Banten, 2018)
The objectives of this research is to know the effectiveness of learning program through Boy-boyan Game (traditional game from West Java Indonesia) to develope interpersonal and intrapersonal intelegency of PHBS Kindergarten and NEO Mahardika Kindergarten students (TK). This research is motivated by the discovery of the potential development of interpersonal and intrapersonal intelligence of Kindergarten students which is not well developed and it’s need to be developed optimally by implementing learning programs Boyboyan game. To formulate the framework program and finding data as material preparation program, so in this study used quantitative approach with quasi experimental methods used against children in group B PHBS and NEO Mahardika that is consisting 20 students as control group 20 students as experiment group. The procedure consists of pre-field research, the implementation of the study, data analysis and reporting the result .Based on the research the researcher found the following result: First, the development of interpersonal and intrapersonal intelligence of kindergarten appeared to vary for each children. Second, the learning program found that the learning program through the traditional game formulations include: rational, goals, objectives and scopes. Third, learning programs through traditional games have a positive effectiveness to improve interpersonal and intrapersonal development of early childhood, from the average obtained that the average experimental group is greater than the control group. It means that interpersonal and intrapersonal intelligence grouped experiment better than the control group or in other words the treatment in the experimental group in the form of learning through traditional games effective in improving interpersonal and intrapersonal intelligence of children. Based on the findings of the above the recommendation of this research is aimed to teachers of kindergarten should enhance the program in accordance with the curriculum related to the themes of learning certain to develop learning activities both theoretical study and practical for children, so that children are able to develop intelligence prominent/dominant in him. For further research should apply the kind of game where the more dominant towards the development of a child's intelligence so that it will appear to optimally increase interpersonal or intrapersonal intelligence of children.